Combustion and kinetic parameters estimation of torrefied pine, acacia and Miscanthus giganteus using experimental and modelling techniques. (November 2017) - Wilk, Małgorzata; Magdziarz, Aneta; Gajek, Marcin; Zajemska, Monika; Jayaraman, Kandasamy; Gokalp, Iskender
Graphical abstract: Highlights: Torrefaction enhances the fuel properties by increasing carbon content and HHV. Combustion properties of raw and torrefied biomass are investigated by TGAs. Combustion kinetics is established. Pollutants from biomass combustion is estimated by Chemkin modelling. Abstract: A novel approach, linking both experiments and modelling, was applied to obtain a better understanding of combustion characteristics of torrefied biomass. Therefore, Pine, Acacia and Miscanthus giganteus have been investigated under 260 °C, 1 h residence time and argon atmosphere. A higher heating value and carbon content corresponding to a higher fixed carbon, lower volatile matter, moisture content, and ratio O/C were obtained for all torrefied biomass. TGA analysis was used in order to proceed with the kinetics study and Chemkin calculations. The kinetics analysis demonstrated that the torrefaction process led to a decrease in Ea compared to raw biomass. The average Ea of pine using the KAS method changed from 169.42 to 122.88 kJ/mol. The changes in gaseous products of combustion were calculated by Chemkin, which corresponded with the TGA results. The general conclusion based on these investigations is that torrefaction improves the physical and chemical properties of biomass.